From Centralization to Decentralization: Blockchain’s Role in Transforming Social Media Platforms - Bidita Sarkar Diba; Jayonto Dutta Plabon; Nishat Tasnim; Mehjabin Hossain; Durjoy Mistry; Sourav Sarker; M. F. Mridha; Yuichi Okuyama; Jungpil Shin (IEEE Access)
Blockchain is influencing the social media platforms by promising to solve the biggest issues of today, such as privacy concerns and content moderation, and the ability to provide a decentralized system for the management of social media platforms through cryptographic techniques and distributed structures. Conventionally, social media systems are based on central architectures that may indirectly solve the problems of data privacy and platform responsibility since there are increased threats, including identity theft and fake news spread across such systems. Blockchain has stepped up as an anti-centralized platform that allows multiple numbers of users to transact securely and authentically through P2P channels without a middleman. Here in this survey, we introduce a brief overview of the latest trends of the blockchain protocols and the interactions with the social media platforms, as well as present a systematic review of the related area. Specifically, the use case we consider and elaborate on is how blockchain can be applied to various types of social media services: smart contract-based content moderation platforms, user incentives using token economics, social media governance through decentralized autonomous organizations, and cross-chain connections. We then go further and offer a comprehensive literature review of blockchain incorporating main social media applications that cutting across them include identity, tokenization, and self-governance. The key points that can be derived from this review of the blockchain-enabled social media services and applications are also underlined here. We conclude this survey by listing the existing issues in the field, including scalability and compliance with the existing regulations, and suggesting the possible areas of research in this ever-evolving field.